Between Guru and Deceiver? Responding to Unchosen Metaphors in the Religious Studies Classroom - Carr, Amy (Teaching theology and religion, 2010)
Two troublesome portraits of religious studies professors often exist in the minds of some students at any given time: the Guru, or wise spiritual teacher, and the Deceiver. These metaphors capture student perceptions of us that may be ill-informed and beyond our control. We will examine and compare how our own chosen metaphors for teaching – theological typologist and neutral enthusiast – respond creatively to the unchosen metaphors of guru or deceiver. We cannot avoid being cast as gurus/deceivers, but we can discern how our own metaphors for teaching engage “unchosen” student metaphors for us. This exercise can enhance our self-awareness about our own normative agendas in the classroom, and help to sharpen colleagues' conversations about our sometimes differing assumptions regarding the discipline and teaching of religious studies.